Ethnoecology of paddy-fish integrative farming (minapadi) in Lampegan Village, West Java, Indonesia - IIK NURUL FATIMAH; JOHAN ISKANDAR; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fatimah IN, Iskandar J, Partasasmita R. 2020. Ethnoecology of paddy-fish integrative farming (minapadi) in Lampegan Village, West Java, Indonesia. Biodiversitas 21: 4419-4432. In the past, the traditional paddy-fish integrative farming (minapadi) was predominantly undertaken by rice farmers in West Java, particularly in the water abundant areas. Currently, however, the practice of the rice-fish system has been dramatically reduced due to the Green Revolution programs, including water pollution that may have affected fish farming in paddy fields. Although the rice-fish systems have rarely been practiced in West Java villages, some farmer groups of Lampegan Village, Ibun Sub-district, Bandung District are still practicing the rice-fish farming system. The purpose of this study is to collect and document the traditional ecological knowledge (TEK) of Lampegan Village about the rice-fish system farming managements, including data on various fish species that are widely cultivated in the community, cultural practices of the rice-fish farming management, and benefits of the rice-fish farming system. A combination of qualitative and quantitative methods was used, with an ethnoecological approach. Techniques of data collection, such as observation, semi-structured interviews, or deep interviews, and structured interviews were employed in this study. The results of the study show that the farmers of the rice-fish farming in Lampegan Village, Bandung District own rich and deep knowledge of fish species and practice of the minapadi system. The TEK of the rice-fish farming management system has been inherited from ancestors and is mixed with western scientific knowledge. The rice-fish farming systems have provided some ecological and socio-economic benefits for village people.